SIADH in Hemorrhagic Stroke Patients: A Case Series - Imran I; Syahrul S; Farida F; Ipak Nistriana (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
Hyponatremia is common in acute stroke, possibly syndrome of inappropriate antidiuretic hormone (SIADH) or cerebral salt-wasting syndrome (CSWS). Hyponatremia is defined as a condition in which the sodium concentration is below 135 mEq/L. Hyponatremia can cause hypoosmolality in cerebral blood vessels and cause an increase in intracranial pressure resulting in cerebral edema which can be life threatening. Patient 1, 47 years old male with a hemorrhagic stroke came to the emergency room at Zainoel Abidin Hospital with acute weakness in the right side (2 hours’ onset) and headache when the patient was working in the office followed by a decrease in consciousness (GCS 14), he is an uncontrolled hypertensive patient, active smoker and rarely physical exercise. His blood pressure was 230/140 mmHg, heart rate, respiration and body temperature were normal, right side neurologic deficit with positive Babinsky reflex. The head CT scan shows intracerebral hemorrhage (ICH) in the left hemisphere. Laboratory examination revealed serum sodium levels of 130 mmol/L, potassium 3.9 mmol/L. During the treatment period, the patient often complained of headaches and frequent vomiting. There were no symptoms of hypovolemia, so it was suspected that the cause of hyponatremia was SIADH and the symptoms improved after fluid restriction and sodium chloride supplementation. After 2 weeks of treatment, the patient was allowed to go home. Patient 2, aged 60 years male with hemorrhagic stroke, came to the emergency room at Zainoel Abidin Hospital with a sudden loss of consciousness on activity (onset 4.5 hours, GCS 11), with vomiting twice, left side weakness, dysarthria, and headache. The patient is an uncontrolled hypertension and diabetes mellitus, blood pressure is 158/102 mmHg with normal heart rate, breathing and body temperature. The Head CT scan showed massive intracerebral and intraventricular hemorrhage in the right hemisphere, serum sodium level of 129 mmol/L, potassium 3.8 mmol/L, and chloride 106 mmol/L, and random blood sugar 226 mg/dL, no hypovolemia was found. The patient had SIADH. After fluid restriction, furosemide and sodium chloride supplementation, the patient's condition improved. Hyponatremia in stroke can be either SIADH or CSWS. These two conditions are similar but require different treatment, therefore they must be determined precisely. Monitoring serum sodium levels and determining the etiology of hyponatremia in stroke patients is very important.